SENI BAHASA DALAM LEKA PELIAN BERDASARKAN PERSPEKTIF TEORI METAFORA KONSEPTUAL: (LANGUAGE ARTS IN “LEKA PELIAN” BASED ON THE PERSPECTIVE OF CONCEPTUAL METAPHOR THEORY) - Yanti Benson; Rosline Sandai; Rohayati Junaidi; Saripah Banseng (Jurnal Pengajian Melayu (JOMAS), 2023)
Abstract “Leka pelian” is a traditional poem of the Iban community in the invocation category, which is used in traditional Iban healing rituals. Every word sung by the “manang” in “leka pelian” is decorated with figurative language and metaphors to add more beauty to the art of poetry. However, the lack of experts in “leka pelian” makes it difficult for the younger generation, especially the Iban community, to understand the figurative language and metaphors used in “leka pelian” by the “manang”. This has led to the younger generation showing less interest in delving into oral traditions such as “leka pelian”. Therefore, this study aims to analyse the meaning of the metaphors that shapes the “leka pelian” based on the conceptual metaphor theory of Lakoff and Johnson (1980). This study is qualitative and uses the Conceptual Metaphor Theory of Lakoff and Johnson (1980) to analyse the categories of metaphors found in “leka pelian”. Content analysis method is used to analyse each category of metaphor found in “leka pelian”. The findings show that the figurative language in “leka pelian” consists of abstract metaphors to reality, simile metaphors, animal metaphors, nature metaphors, as well as adapted and cultural comparison metaphors in their lives. The investigation shows that nature metaphors are more dominant than other metaphors because they are influenced by the surrounding nature, making nature a metaphor in communication. This category of metaphor is also used as a medium of communication between human world and the supernatural world. The implication of this research shows that the use of different categories of metaphor in “leka pelian” can increase the knowledge of traditional healers and the Iban community, especially in terms of language skills. Keywords: Metaphor; Figurative Language; Leka Pelian, Conceptual Metaphor Theory Abstrak Leka pelian merupakan puisi tradisional masyarakat Iban dalam kategori invokasi yang digunakan dalam ritual perubatan tradisional Iban. Setiap perkataan yang dilagukan oleh manang dalam leka pelian digayakan dengan bahasa kiasan metafora bagi menambahkan lagi keindahan seni berpuisi. Namun begitu, kekurangan golongan yang arif dalam leka pelian menyukarkan generasi muda khususnya masyarakat Iban kurang memahami bahasa kiasan metafora yang terdapat di dalam leka pelian yang dilagukan oleh manang. Perkara tersebut menyebabkan generasi muda kurang berminat dalam mendalami tradisi lisan seperti leka pelian. Oleh itu, kajian ini bertujuan menganalisis maksud metafora yang membentuk leka pelian berdasarkan teori metafora konseptual Lakoff dan Johnson (1980). Kajian ini berbentuk kualitatif dengan menggunakan Teori Metafora Konseptual Lakoff dan Johnson (1980) untuk menganalisis kategori metafora yang terdapat di dalam leka pelian. Kaedah analisis kandungan digunakan untuk menganalisis setiap kategori metafora yang terdapat di dalam leka pelian. Dapatan kajian menunjukkan bahasa kiasan leka pelian terdiri daripada metafora abstrak ke realiti, metafora perumpamaan, metafora berunsurkan haiwan, metafora alam dan metafora perbandingan yang disesuaikan dicipta serta menjadi budaya dalam kehidupan mereka. Dapatan kajian menunjukkan bahawa metafora alam lebih dominan berbanding metafora yang lain kerana dipengaruhi oleh alam sekeliling yang menjadikan alam sebagai kiasan dalam berkomunikasi. Kategori metafora ini juga digunakan sebagai medium komunikasi antara alam manusia dengan alam ghaib. Implikasi kajian ini menunjukkan bahawa penggunaan kategori metafora dalam leka pelian dapat menambahkan pengetahuan pengamal perubatan tradisional dan masyarakat Iban khususnya tentang kemahiran berbahasa. Kata Kunci: metafora; bahasa kiasan; leka pelian, Teori Metafora Konseptual